2019
DOI: 10.1021/acs.analchem.9b01130
|View full text |Cite
|
Sign up to set email alerts
|

Counting and Recognizing Single Bacterial Cells by a Lanthanide-Encoding Inductively Coupled Plasma Mass Spectrometric Approach

Abstract: Counting and recognizing single bacterial cells are crucial to the diagnosis of bacterium-induced disease and study of cell-to-cell variability as well as the related antibiotic resistance mechanism. A higher sensitive and selective method has always been desired for a more accurate single bacterial cell analysis. We report a lanthanide-encoding inductively coupled plasma (ICP) mass spectrometric approach for counting and recognizing single bacterial cells for the first time. When noncanonical alkyne-d-alanine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Nowadays, this technique has been proven to be a versatile tool for studies on the determination of constitutive elements, the cellular uptake of metal-containing drugs, and the incorporation of metallic nanoparticles . In combination with labeling strategies, further studies have shown the versatility of this technique in characterizing individual cells or bacteria. The development of novel elemental tags that allow increased sensitivity is currently an active field of research. Besides polymers or metal nanoparticles, other nanostructures can be used to allocate a large number of tag-element atoms, such as viruslike nanoparticles …”
mentioning
confidence: 99%
“…Nowadays, this technique has been proven to be a versatile tool for studies on the determination of constitutive elements, the cellular uptake of metal-containing drugs, and the incorporation of metallic nanoparticles . In combination with labeling strategies, further studies have shown the versatility of this technique in characterizing individual cells or bacteria. The development of novel elemental tags that allow increased sensitivity is currently an active field of research. Besides polymers or metal nanoparticles, other nanostructures can be used to allocate a large number of tag-element atoms, such as viruslike nanoparticles …”
mentioning
confidence: 99%
“…These low-abundance substances often play important roles in their corresponding chemical or biological systems (Chen et al, 2016;Finn et al, 2020;Marabelle et al, 2020). Accurate and sensitive analysis of these low-abundance substances is essential for the in-depth interpretation of related chemical and biological phenomena (Sonnett et al, 2018;Yin et al, 2018;Liang et al, 2019). Therefore, there are great demands for analytical instruments with higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, to guarantee the accurate homogeneous immunoassay, a self-validated immunoassay was proposed by simultaneously scrutinizing both the frequency and the intensity of the pulse signal from single gold nanoparticles (AuNPs). The metal isotopes inside nanoparticle tags were sensitively and selectively detected by inductively coupled plasma mass spectrometry (ICPMS), which has been recently successfully demonstrated in the analysis of metals, , proteins, nucleic acid, , enzymes, single cells, etc. The frequency of the pulse signals represents the number concentration of AuNPs, while the recorded signal intensity represents the size of AuNPs. , Carcinoembryonic antigen (CEA), a 180 kDa glycoprotein which belongs to tumor-associated biomarkers in human serum, was selected as a model analyte.…”
mentioning
confidence: 99%